Identifikasi Komponen Minyak Atsiri Daun Salam (Syzygium polyanthum (Wight Walp.) dengan GC-MS dan Potensinya Sebagai Antibakteri - Sihotang, Santyria; Simanjuntak, Helen Anjelina; Purba, Hermawan; Iksen, Iksen; Sembiring, Mahral Effendi (Herbal Medicine Journal, 2025)
Essential oils, known as volatile oils or essential oils, are oils produced from plants and have the property of easily evaporating at room temperature without undergoing decomposition. The bay leaf plant (Syzygium polyanthum (Wight.) Walp.) is one of the plants that is very often used as an alternative medicine. There is evidence that bay leaves, which contain compounds such as niacin, fiber, tannin, and vitamin C, have the ability to lower serum triglyceride levels. This research aims to determine the essential oil content in bay leaves using the steam distillation method and its potential as an antibacterial. The results of the research show that bay leaves contain essential oils which have antibacterial properties against the bacteria Helicobater pylori and Bacillus cereus. Bay leaf essential oil (Syzygium polyanthum (Wight.) Walp) with varying concentrations of 10%, 30%, 50%, 70% and 100% showed the highest inhibitory zone diameter for Helicobater pylori bacteria, namely at a concentration of 100% with a diameter of 5, 25 mm and in Bacillus cereus bacteria with a diameter of 7.95 mm.